2017
DOI: 10.1177/0300060517714935
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the validity of the Triage Risk Screening Tool in a third world setting

Abstract: BackgroundSocial risk is rarely evaluated in older emergency department (ED) patients, although its identification can reduce re-attendance.ObjectivesThis study assessed the diagnostic accuracy of the Triage Risk Screening Tool (TRST) in the ED of a developing country.MethodsThe diagnostic accuracy of the TRST to detect elderly adults in need of social service intervention was compared with routine clinical evaluation, using comprehensive evaluation by an experienced social worker as the “gold standard”. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Study authors were contacted regarding administration time if clarification was needed from the research article. Some of the instruments were ultra-short to administer (<2 min), such as the Bergman Paris Question (BPQ) [ 35 ] and Variable Indicator of Risk Placement (VIP) [ 10 , 37 , 38 ], while others were performed in more than one stage, such as the Triage Risk Screening Tool (TRST) [ 36 ], with its initial screen, the Emergency-TRST (E-TRST), usually taking less than 2 min [ 39 ]. From previous studies in ED, usual administration times for the ISAR vary from 2 to 5 min [ 40 ], while the FRESH instrument is recorded as taking ≤5 min [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Study authors were contacted regarding administration time if clarification was needed from the research article. Some of the instruments were ultra-short to administer (<2 min), such as the Bergman Paris Question (BPQ) [ 35 ] and Variable Indicator of Risk Placement (VIP) [ 10 , 37 , 38 ], while others were performed in more than one stage, such as the Triage Risk Screening Tool (TRST) [ 36 ], with its initial screen, the Emergency-TRST (E-TRST), usually taking less than 2 min [ 39 ]. From previous studies in ED, usual administration times for the ISAR vary from 2 to 5 min [ 40 ], while the FRESH instrument is recorded as taking ≤5 min [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lalla et al 22 reported on the use of another triage tool, but this time in geriatric patients, an increasingly important patient cohort in low-and middle-income countries. They found that the Triage Risk Screening Tool was more accurate in detecting elderly patients in need of a social services intervention at the time of discharge from the ED when compared to routine assessment.…”
Section: Discussionmentioning
confidence: 99%